The need for learners to understand their readiness for open and distance learning - Lim , Tina Swee Kim (2009)
Open and distance learning programmes are often faced with high attrition rates amongst learners. Studies suggest that a number of causative factors contribute to students dropping out from courses, even as early as the second semester. Factors that have been identified generally fall under personal, family and institutional categories. While open and distance learning education providers appear to try and address this problem using numerous strategies, one particular aspect that seems to have been generally neglected but ought to be given due attention is helping students understand their readiness for open and distance learning. This paper seeks to describe a pilot project whereby open and distance learners are provided with an online self-assessment tool which measures aspects deemed important to open and distance learning, that is, their (1) personal attributes such as time management, procrastination, academic attributes, persistence, locus of control and willingness to ask for help, (2) preferred learning styles based on the multiple intelligences model, (3) basic instructional technology knowledge and skills, and (4) typing speed and accuracy. The tool also provides a complete report detailing their strengths and opportunities for improvement as well as resources to succeed. It is envisaged that the provision and use of such a tool would help learners better prepare themselves to open and distance learning environments and thereby help ensure they have a successful learning experience. (Authors' abstract)